Exploring Teacher Strategies in Teaching Descriptive Writing in Indonesia (Malaysian Journal of Learning and Instruction, 2016)
Purpose â€“ This paper is the outcome of a study which examined teacher strategies in teaching descriptive writing to junior high school students in Delitua, North Sumatra, Indonesia. The study was based on two questions: 1) What are the teaching strategies used by EFL teachers in teaching descriptive writing? 2) To what extent did the descriptive writing intervention change the EFL teacher teaching strategies? Methodology â€“ The qualitative data were obtained from observations, interviews and student writing. An intervention conducted with four teachers for four months using Spencerâ€™s Writing Model (2005) to enhance the teaching of writing strategies was examined. The data were recorded, transcribed verbatim and analyzed using thematic coding. Findings â€“ The findings revealed that the teachers used limited strategies in teaching writing due to their lack of knowledge and understanding of the writing approaches. However, after the writing intervention, they improved their instructional strategies by incorporating richer writing descriptions which contained sensory details, figurative language and vivid words. Significance â€“ These findings can be used as teaching guidelines for EFL writing in any teacher professional development programmes. Training of teachers could be a starting point not only to increase teachersâ€™ knowledge and skills in teaching writing but also to increase their awareness of the beliefs about teaching and learning. Our study provided evidence that training can bring about changes in teachersâ€™ pedagogical practices which in turn, will lead to a more meaningful learning environment for their learners.